Analysis On Stress-Strain Performance Of ABS/PLA Material Used In Geospatial Solution - Salim, Mohd Azli; Termiti, Zarif Hasif; Md. Saad, Adzni; Omar, Ghazali (Universiti Teknikal Malaysia Melaka, 2018)
This paper presents tensile testing measurement on two type FDM filament material which are ABS and PLA.Tensile testing was conducted according to ASTM D638 by using Universal testing Machine for testing both material under tensile loading in order to determine the material properties.Based on the result,both of the material behavior shows the material break of fail after yield occur.The PLA material has higher value of tensile strength,yield strength and modulus of elasticity compare to ABS Material.The performance show by PLA material is greater than ABS material because the tendency of PLA material to exert amount of force before failure is higher,the ability to resist plastic deformation is higher due to high yield strength and has high stiffness due to high value of modulus elasticity.